Stability of Jungck-type iterative procedures - S. L. Singh; Charu Bhatnagar; S. N. Mishra (International Journal of Mathematics and Mathematical Sciences)
We introduce and discuss the stability of Jungck and Jungck-Mann iterative procedures for a pair of Jungck-Osilike-type maps on an arbitrary set with values in a metric or linear metric space.